76 Granular cell tumor, a rare breast tumor. (13th November 2020) - Gomez, M; Mehta, R
Abstract : Introduction: Granular cell tumors involving the breast parenchyma are very uncommon, accounting for 5% to 8% of all granular cell tumors. They are benign neoplasms usually presenting clinically and radiologically as a mass indistinguishably from cancer, representing a big diagnostic challenge where histological evaluation becomes essential to differentiate between both. Case Report: We report a case of a 46-year-old female with no relevant past medical clinical history, who underwent a routine mammogram revealing a 0.4 × 0.4 × 0.3 cm irregular mass in her left breast, concerning from malignancy. Histological examination and immunohistochemical studies proved this to be a granular cell tumor. The lesion was successfully excised, and patient recovered with no further major health implications. Conclusion: Although this entity is infrequent, it should be taken in consideration as a differential diagnosis when confronting with a breast mass in a young patient. Pathological assessment is of utmost importance in order to establish an accurate diagnosis, especially preoperative, potentially sparing the patient from a more invasive surgical procedure that could have repercussions not only physically but also emotionally.